2015
DOI: 10.1186/s12913-015-0982-1
|View full text |Cite
|
Sign up to set email alerts
|

The importance of older patients’ experiences with care delivery for their quality of life after hospitalization

Abstract: BackgroundOlder patients’ experiences with care delivery may be important for their quality of life over time. Evidence is however lacking. Therefore, this study aims to identify the longitudinal relationship between older patients’ experiences with hospital care, perceived quality of integrated care and quality of life after hospitalization.MethodsOur longitudinal research was based on a pilot study of older people who had recently been admitted to a hospital. In the pilot study, all patients (≥65 years of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 53 publications
1
29
1
3
Order By: Relevance
“…This positive association in terms of process and outcome quality applies to all of the analysed dimensions of patient satisfaction (satisfaction with medical care, nursing care, organization and service, and in general/recommendation). Similar results were reported by international studies, which indicated a positive association between clinical quality characteristics and patient satisfaction . The results of this study did therefore not confirm the opinion often expressed by critics that patient satisfaction may only be influenced by external factors such as hotel services .…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…This positive association in terms of process and outcome quality applies to all of the analysed dimensions of patient satisfaction (satisfaction with medical care, nursing care, organization and service, and in general/recommendation). Similar results were reported by international studies, which indicated a positive association between clinical quality characteristics and patient satisfaction . The results of this study did therefore not confirm the opinion often expressed by critics that patient satisfaction may only be influenced by external factors such as hotel services .…”
Section: Discussioncontrasting
confidence: 62%
“…Patient satisfaction can provide valuable and unique insights into daily hospital care and is widely accepted as an independent dimension of quality of care because an evaluation of patient satisfaction includes “internal” (inward‐looking) aspects of hospital care, which often remain unrecorded, such as communication, empathy or interaction . Numerous studies and systematic reviews demonstrate, however, a positive association between the subjective patient perspective and clinical safety and effectiveness, and they demonstrate that patient satisfaction reflects various dimensions of the quality of care …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenges include providing continuity of care, with dignity and compassion (Levenson, ; Firth‐Cozens & Cornwell, ; Abraham, ; Care Quality Commission, ; Francis, ). Breakdowns in continuity of care put patients at risk of functional decline (Hartgerink et al ., ) and add avoidable costs to both health care and social care (JRF, ). This study focuses on carer engagement as a possible way to address some of the challenges of delivering hospital care to older people.…”
Section: Introductionmentioning
confidence: 96%
“…By offering functional rehabilitation or convalescence, where possible the SSR units aim at fostering a patient's return to his or her home. Indeed, entering hospital is often accompanied by a deterioration of functional autonomy and increased dependency (Berkman, Leipzig, Greenberg, & Inouye, 2001) or rapid admission into a nursing home, and increased mortality (Hartgerink, Cramm, Bakker, Mackenbach, & Nieboer, 2015), and one of the functions of these units is to help prevent these negative outcomes. Autonomy is thus considered as an important outcome strongly associated with the idea that older people should be allowed or enabled to make autonomous decisions about their health care (Beauchamp & Childress, 2009;Pardessus, Durocher, & Di Pompeo, 2000).…”
Section: Introductionmentioning
confidence: 99%